Analisis Pengaruh Integrasi Artificial Intelligence dan Pengembangan Kompetensi Generasi Z terhadap Keberlangsungan Organisasi - Resi Khalisya Wildani; Fajar Rudiyanto; Oktaviona Salsabrina; Ridki Riandi; Retno Purwani Setyaningrum (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study uses a quantitative approach with a survey method. Data were obtained from 50 respondents who are Generation Z employees and work in various organizational sectors in Indonesia. The sample size was determined using the Lemeshow formula because the study population is not known with certainty. Data analysis was carried out using the Partial Least Square (PLS) method with the help of SmartPLS 4.0 software. The results of the study indicate that AI integration does not have a direct significant effect on organizational sustainability, but has a positive and significant effect on Generation Z involvement which in turn has a significant effect on organizational sustainability. Meanwhile, the development of digital competencies does not show a significant effect either directly on organizational sustainability or indirectly through Generation Z involvement. This finding indicates that the application of technology in organizations does not necessarily directly guarantee organizational sustainability without being accompanied by employee involvement, especially Generation Z. This study is expected to provide theoretical contributions in the development of technology-based human resource management studies and provide practical implications for organizations in designing sustainable digital transformation strategies.